In vitro activity of compounds isolated from Piper crassinervium against Trypanosoma cruzi - Lopes, Adriana Aparecida [UNESP]; Lopez, Silvia Noeli [UNESP]; Regasini, Luis Octavio [UNESP]; Batista Junior, Joao Marcos [UNESP]; Ambrosio, Daniela Luz [UNESP]; Kato, Massuo Jorge; Bolzani, Vanderlan da Silva [UNESP]; Barretto Cicarelli, Regina Maria [UNESP]; Furlan, Maysa [UNESP] (Taylor & Francis Ltd, 2008)
This study describes the antichagasic potential of five compounds isolated from leaves of Piper crassinervium (Piperaceae). Two prenylated benzoic acid derivatives, one prenylated hydroquinone and two flavanones, were evaluated. The in vitro trypanocidal activity was determined against epimastigote forms of Trypanosoma cruzi (Y strain), the etiologic agent of Chagas disease. The most active compound was the prenylated hydroquinone [1,4-dihydroxy-2-(3(0),7(0)-dimethyl-1(0)-oxo-2(0)-E,6(0)-octadienyl)benzene] with an IC(50) value of 6.10 g mL(-1), which was in the same order of activity if compared with the positive control benznidazole (IC(50) = 1.60 mu g mL(-1)). This is the first report of trypanocidal activity for prenylated hydroquinone and benzoic acid derivatives.
Keywords: prenylated benzoic acid; prenylated hydroquinone; flavanone; Trypanosoma cruzi; Piper crassinervium